Investigation of Moisture Sensitivity and Conductivity Properties of Inductive Asphalt Mixtures Containing Steel Wool Fiber. (31st October 2020) - Hosseinian, Seyed Mohsen; Najafi Moghaddam Gilani, Vahid; Mehraban Joobani, Peyman; Arabani, Mahyar
Abstract : The construction of suitable roads in rainy areas has created problems in the construction process due to the low resistance of asphalt to moisture. To solve this problem, materials are commonly used that make mixtures resistant to moisture; however, these materials may reduce the dynamic resistance of asphalt. Therefore, materials should be used that, in addition to increasing the dynamic resistance, also increase the moisture resistance of asphalt mixtures. One of these materials used in this research is steel wool fiber (SWF), which in addition to creating conductive roads also could have a significant effect on moisture resistance. In this study, the impact of 2%, 4%, 6%, 8%, and 10% SWF on the Marshall stability and moisture sensitivity of mixtures was investigated using the Marshall stability and indirect tensile strength (ITS) tests, respectively. Moreover, using SWF as a conductive fiber, the conductivity properties of asphalt mixtures were explored to find the optimal amount of electrical conductivity. The results of the Marshall stability test indicated that by increasing SWF contents, the stability of mixtures increased, compared with the base sample, and greater amounts of 6% SWF resulted in the reduction of the Marshall stability. The results of ITS showed that modification of bitumen by SWF increased ITS and tensile strength ratio (TSR) amounts of mixtures. 6% SWF was the optimal amount for enhancing the resistance of asphalt mixtures to moisture sensitivity. The results of the electrical resistivity test showed that the resistivity had three phases: high resistivity, transit, and low resistivity. Mixtures containing less than 4% SWF illustrated an insulating behavior, with electrical resistivity greater than 7.62 ×  10 8  Ω . m . At the transit phase, the resistivity of mixtures had a sharp reduction from 7.62 ×  10 8  Ω . m to 6.17 ×  10 4  Ω . m . Finally, 8% SWF was known as the optimal content for the electrical conductivity of mixtures.